COMPARATIVE STUDY OF CLOUD COMPUTING NETWORK SERVICES BASED ON QoS ANALYSIS USING TIPHON STANDARD - Aziza, Rosida Nur; Jaya Adilman; Djunaidi, Karina; Sudirman, M.Yoga Distra; Yusra, Muhammad Danial (Informatika, Universitas Jenderal Soedirman, 2023)
Currently, data plays a very important role for companies or agencies. The amount of data owned, processed, and exchanged is getting bigger, so companies need more and more resources to manage it. Cloud computing technology is an efficient and economical alternative that allows users to utilize Information Technology (IT) resources flexibly, in terms of infrastructure and applications. Its key advantages include cost efficiency, scalability, data security, disaster recovery, and fast global access. The rapid development of cloud technology has led to many Cloud Service Providers (CSPs). The performances of the CSPs vary widely, thus it is necessary to understand the network performance characteristic from the CSPs so that users can select a more suitable service. Network capabilities in cloud computing technology are crucial, considering that all company activities are carried out through the network. In this study, the main focus was to test the network capabilities of the two biggest cloud services The results of the Quality of Service (QoS) comparison will provide recommendations or input for companies or agencies in choosing the cloud service provider that best fits their needs. Thus, it was obtained that this research can provide useful guidance in optimizing the use of cloud computing technology to support business activities and innovation in various fields, including the field of education. Based on the results of the research, the network performance of the two CPS is very good in terms of the TIPHON standard. Based on QoS analysis, especially in terms of throughput, CPS “A” shows better upload activity results, while CPS B has better results for downloading activities.